Analisis Pencatatan Keuangan Sederhana pada UMKM Kelurahan Naga Pita Kecamatan Siantar Martoba Kota Pematangsiantar - Lince Hotmaria Hutabarat; Nanda Sukira Rezki Manurung; Yusmalinda Yusmalinda (INDO PUBLISHING, 2026)
This study aims to analyze the implementation of simple financial record-keeping among MSMEs in Naga Pita Subdistrict, Siantar Martoba District, Pematangsiantar City. The research employed a descriptive approach through observation and interviews with 93 MSMEs selected using the Slovin formula with a 10% margin of error. The results show that 59 MSMEs (63%) have not implemented financial record-keeping, while 34 MSMEs (37%) have applied simple records with varying levels of completeness (complete, moderate, and limited). MSMEs that implement financial record-keeping tend to have better financial control, clearer profit identification, and more structured business planning. In contrast, those without records rely mainly on experience and memory in decision-making. The findings indicate that simple financial record-keeping plays an important role in improving business management effectiveness and sustainability.